Public debt and growth: heterogeneity and non-linearity - Eberhardt, Markus; Presbitero, Andrea F. (Elsevier, 2015)
We study the long-run relationship between public debt and growth in a large panel of countries. Our analysis builds on theoretical arguments and data considerations in modelling the debt-growth relationship as heterogeneous across countries. We investigate the debt-growth nexus adopting linear and non-linear specifications, employing novel methods and diagnostics from the time-series literature adapted for use in the panel. We find some support for a negative relationship between public debt and long-run growth across countries, but no evidence for a similar, let alone common, debt threshold within countries.